DESIGN OF SMALL DUAL BAND SLOT ANTENNA: dual-band antenna - Mabroka BOBREEG; Amer, fathia (Surman Journal of Science and Technology, 2025)
This paper aims to design a slot antenna having small dimensions with dual bands, dual-band antennas allow you to connect wirelessly for tighter access to locations and are often used for devices such as cellular or dual-band wireless access points, the antenna works at 3.1 and 5.4 GHz and their geometry consists of a rectangular slit associated with the broad part of the L -shaped slot fed by a 50-ohm micro-strip line and another rectangular slit scratched at the base of the ground plane connected, the length of the first rectangular slit is set to be around 1/4λ at the lower frequency f1 = 3.1GHz, while the length of the second slit is set to be around 1/4λ at the upper-frequency f2 = 5.4GHz, the antenna printed on a 0.8 mm of FR4 substrate thickness with relative permittivity 4.4. In this paper, we simulated and designed a small dual-band slot antenna with a small size and good outcomes( the return losses s11 were -22 dB and -15 dB at frequencies 3.9 and 5.5 GHz, respectively,). The design parameters of the antenna used the transmission line model, and HFSS electromagnetic software was used for the simulation process.